(untitled) (Indian Journal of Experimental Biology (IJEB), 2021)
Though grafting in plants is in practice since ages only limited information is available on the graft-induced morphological, biochemical and molecular variations. The mechanism(s) by which rootstocks influence scion vegetative growth and development, and vice versa, are not fully understood. Therefore, in the present investigation, we studied graft- induced variations in different apple stionic combinations using scion (Scarlet Gala and Red Fuji) and rootstocks (MM111, MM106, M7, M9 and M26). Under morphological variations, significant difference was found in all the parameters viz. leaf area, shoot length, internodal length and fruit characters except petiole length and fruit firmness. Likewise, significant difference was also observed in the subjected stionic combinations based on total phenolic contents, total free amino acids and peroxidase enzyme activity. These results were further validated using DNA based molecular markers SSR. However, no polymorphism was observed in both the stionic combinations at DNA level. These results imply that rootstocks may influence morphological and biochemical parameter of the scion during graft-union but it does not influence genetic constitution of scion at DNA level. Further studies at RNA or protein level are required to unravel the reasons behind these variations.